2001
DOI: 10.1111/1467-6427.00168
|View full text |Cite
|
Sign up to set email alerts
|

Understanding alliances. How can research inform user‐friendly practice?

Abstract: 'User-friendliness' is described as a therapist stance which involves attentiveness to the quality of the 'therapeutic relationship', both between therapist and family and between service providers and their public. This article draws on research published in the last seven years from within and outside the family therapy field which can help improve this relationship. I will argue that the issues which challenge user-friendly practice need to be related to the theories which inform family therapy and to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Recent research by Everall and Paulson (2002) has found that such techniques are useful with ‘hard to engage’ clients. It is also important to note that some cognitive therapists argue that before carrying out ‘active cognitive therapy’ techniques, it is important to establish a therapeutic alliance from which to work (Rector, Zuroff, & Segal, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research by Everall and Paulson (2002) has found that such techniques are useful with ‘hard to engage’ clients. It is also important to note that some cognitive therapists argue that before carrying out ‘active cognitive therapy’ techniques, it is important to establish a therapeutic alliance from which to work (Rector, Zuroff, & Segal, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The idea that the patient is a consumer of mental health services is not new, but the implications this has for the relationship has not been studied a great deal. 120 The concept of 'user-friendliness' has been developed as a process by which patients are asked specifically about the quality of their relationship with their therapist. 91…”
Section: Patient Rolesmentioning
confidence: 99%
“…As Reimers (2001) points out, one alternative to simply removing families from the waiting list is the offer of an alternative and shorter service. Stallard and Sayers (1998) offered families on a child psychiatry waiting list the option of either confirming that they CLINICAL CHILD PSYCHOLOGY AND PSYCHIATRY 9(3) wished to stay on the list (and wait an average over five and a half months), or opt for an immediate assessment and treatment of three sessions.…”
Section: Systemic or Clinic-related Factorsmentioning
confidence: 99%